Depth-Dependent Optical Stiffness Toward Water-Air Interface - Yeng, M. S. Mat; Ayop, S. K.; Mustapa, I. R. (International Journal of Engineering and Technology, 2018)
This research attempted to quantify the optical stiffness of trapped polystyrene bead toward water-air interface. The optical tweezers with 975 nm wavelength was used to optically trap a single 3 micron diameter of bead in a water-contained cell with air exposed top water surface. The optical stiffness was justified on effective radius (r*) of the bead lateral spatial distribution. The scattered light signals due to the trapped bead at different laser focus height from the bottom glass-water interface (less than 20 Âµm) and laser trapping powers (1.7 mW to 7.5 mW) were analyzed to investigate the r* profile. It was found that within our experimental condition, r* was independent of focus height at fixed power and exponentially decay with respect to laser power at fixed focus height.